LA TEORÍA DE OCKHAM SOBRE LA COGNICIÓN SENSITIVA Y LA RACIONALIDAD ANIMAL NO-HUMANA. - Deni Gamboa, Lydia (Revista Española de Filosofía Medieval, 2019)
For Ockham, every animal has a sensitive soul, in virtue of which it can have sensitive desires, sensitive intuitive cognitions, and sensitive abstractive cognitions. Among the latter cognitions, there are sensitive representations, acts of common sense and memories. This article reconstructs Ockham's theory of animal cognition. The reconstruction shows that Ockham ascribes to animals the capacity of representing different properties of singular things, an episodic memory, a procedural memory and a certain sort of illusion. Since some sensitive representations are equivalent to mental propositions, according to Ockham, non-human animals can judge and form syllogisms.